Angelica Injection Promotes Peripheral Nerve Structure and Function Recovery with Increased Expressions of Nerve Growth Factor and Brain Derived Neurotrophic Factor in Diabetic Rats - Li, Ruilin; Zhang, Junjian; Zhang, Lei; Cui, Qin; Liu, Hui (Current Neurovascular Research, 2010)
Several nervous system injury models, such as sciatic crush and chronic cerebral hypoperfusion have been well studied in terms of neuroprotective effect of angelica injection. However, definitive experimental studies are lacking on diabetic peripheral neuropathy (DPN). This study sought to investigate the effects of angelica injection on DPN in type 1 diabetic rats. Diabetes was induced by single intraperitoneal injection of streptozotocin (STZ). To examine whether DPN model successed, tail-flick latency (TFL) and motor nerve conduction velocity (MNCV) were measured at 6 weeks after diabetes induction. Then, diabetic rats were treated with high- and low-dose angelica injection for 4 weeks. TFL, MNCV, morphology of sciatic nerve, myelinated nerve fiber density and the expressions of nerve growth factor (NGF) and brain derived neurotrophic factor (BDNF) in soleus and sciatic nerve were measured at 10 weeks after diabetes induction. The results showed the TFL was significantly shortened (p< 0.001) and the MNCV was reduced (p< 0.01) in diabetic rats compared with normal control rats at 6 weeks after diabetes induction. The TFL was obviously prolonged and the MNCV was further reduced in diabetic control group at 10 weeks after diabetes induction. TFL, MNCV and morphology of sciatic nerve were remarkably ameliorated and myelinated nerve fiber density and the expressions of NGF and BDNF in soleus and sciatic nerve were increased in the angelica treatment groups. This study suggests angelica injection has potential therapeutic effects on DPN, and the mechanism might be related to direct increase in NGF expression and direct or indirect increase in BDNF expression.
Keywords: nerve growth factor